Primary Sclerosing Cholangitis - Lazaridis, Konstantinos N; LaRusso, Nicholas F (The New England journal of medicine, 2016)
This review summarizes the current understanding of primary sclerosing cholangitis, a persistent, progressive disease for which there is no definitive therapy. The authors describe the pathogenesis and management of this condition. Primary sclerosing cholangitis is an idiopathic, heterogeneous, cholestatic liver disease that is characterized by persistent, progressive, biliary inflammation and fibrosis. There is no effective medical therapy for this condition. 1 End-stage liver disease necessitating liver transplantation may ultimately develop in affected patients. 2 The cause and pathogenesis of primary sclerosing cholangitis are unclear, although it is generally accepted that both genetic and environmental risk factors contribute to the development of the disease as well as to its progression and outcomes. 3 Primary sclerosing cholangitis is strongly associated with inflammatory bowel disease (70 to 80% of patients have both conditions), and it is a . . .